Analysis of the Characteristics of the Development of Web-Based Science Learning Media with the STEAM Approach - Wilem Rilexen S P Mulder; Nur Khoiri; Muhammad Syaipul Hayat (Postgraduate, University of Mataram, 2023)
This research aims to analyze the characteristics of developing Web-Based Science Learning Media using the STEAM approach. This research is development research using the Research and Development (R&D) method with the Thiagarajan 4-D Model which consists of definition, design, development and implementation. Based on the validation results from experts and practitioners, the results are very suitable for use and have character because they have an attractive design, ease of use, and color selection that utilizes color psychology. The features provided are very responsive to learning needs, with an effective project-based STEAM learning flow using scaffolding. Users also have access to Google Data Studio to monitor the progress of each student's STEAM stages and processes. Discussion forums provide flexible interaction and feedback, while STEAM learning modules can be downloaded by teachers for more specific learning situations. The conclusion is that the website developed has unique and unique characteristics that combine color, a project-based STEAM learning flow with a real-time scaffolding system and presents features that make it easier for students to learn